Ultra-broadband non-collinear optical parametric oscillators: A reliable source of rapidly tunable femtosecond laser pulses - Mevert R.; Geesmann F. J.; Lang T.; Binhammer Y.; Zuber D.; Morgner U. (EPJ Web of Conferences)
Non-collinear phase matching in optical parametric oscillators enables unique possibilities ranging from ultra-broadband rapid spectral tuning to intrinsic advantages in power scaling. This work is an overview of this concept adapted to different wavelength ranges.